Mobile LAN based on BLE-configurable wireless Wi-Fi modules - Lykhotop, Denys (Видавництво Львівської політехніки, 2017)
Cyber-physical systems should be able to integrate into a local, wireless network, which can work in the absence of a global Internet, to solve and redistribute common tasks and exchange information among themselves. The presented network is implemented in two versions (compatible with each other as they work in a similar way using the same data packages) on ESP8266 and ESP32 modules. The second one is more functional, flexible to use and configurable with built-in Bluetooth 4.2. The network supports up to 16 simultaneously connected devices (clients). Each WIFI module contains both client and server programs and has an automatic deployment mode. The user interface is an Android mobile application that performs the search for access points, connections, network configuration via BLE, and TCP/IP connections to manage devices connected to network modules, and to monitor information in a convenient way. At the same time, the network is easy to integrate into any system for UART, it is low-power consuming and it also has a low cost of components.
Keywords: Mobile LAN; WI-FI modules; TCP/IP; Bluetooth Low Energy; GATT; multi-agent system